Solvent‐ and catalysts‐free immobilization of tannic acid and polyvinylpyrrolidone onto PMMA surface by DBD plasma. Issue 9 (10th February 2017) - Klébert, Szilvia; Károly, Zoltán; Késmárki, András; Domján, Attila; Mohai, Miklós; Keresztes, Zsófia; Kutasi, Kinga
Abstract : Polyvinylpyrrolidone (PVP) and tannic acid (TAN) macromolecules were attached to polymethyl methacrylate (PMMA) surface in a two‐step approach in order to establish a tailored tissue‐friendly surface layer. First PMMA surface was activated by an air diffuse coplanar surface barrier discharge plasma and subsequently coated with these macromolecules. PVP and TAN which has antibacterial effects are widely used in food and drug industry, however, have never applied for polymer surface modification. Throughout characterization measurements confirm that during plasma treatment oxygen containing functional groups (OH, CO, COOH) incorporate in the surface. 1 HNMR spectroscopy verified the strong H‐bonds between PVP and TAN, which rendered the layer‐by‐layer assembly of these molecules. The roughness increased considerably during plasma treatment, which can promote the further reactions with organic molecules. Abstract : Surface activation polymethyl methacrylate (PMMA) by diffuse coplanar surface dielectric barrier discharge (DCSDBD) plasma unit and subsequent attachment of polyvinylpyrrolidone (PVP) and tannic acid (TAN) macromolecule layers to the surface is studied. Interaction between the two macromolecules is also analyzed by NMR.